Early dynamics of recovery from psychotic spectrum disorder within a therapeutic recovery community: patterns and dynamics. Issue 1 (2nd January 2016) - Snyder, Matt; Young, Sharon; Schactman, Lisa
Abstract : This study reports a detailed analysis of the dynamics of early (3 month) recovery for individuals with psychotic spectrum disorder diagnoses within an integrated, recovery-oriented therapeutic community setting. One hundred and four residents completed a broad suite of measures representing three different definitions/facets of recovery (symptom-, function- and personal recovery-focused) at baseline and at 3 months. Baseline scores and change over the three-month study period correlated more strongly and consistently within the same facet (i.e. symptom-focused to symptom-focused) than between facets (i.e. symptom-focused to functioning-focused). The relatively moderate correlations of the personal recovery-oriented scales supports the view that personal recovery consists of a multitude of overlapping dimensions. These results also suggest heterogeneous pathways of recovery occurring along uncorrelated individual trajectories. Finally, this study offers strong support for the independence of these three facets of recovery within this population.